Jadwal Keberangkatan Kereta Api berbasis Multimedia - Arya Putra, Muhammad; Marlina, Marlina; Wafiah, Andi (Fakultas Teknik Universitas Muhammadiyah Parepare, 2024)
People often have difficulty purchasing and remembering train departure schedules, especially those with busy and complex trips. The purpose of this research is to create a multimedia-based train departure schedule reminder application that is able to handle ticket availability properly and provide accurate information. This research uses a qualitative method based on a literature study and observation for two months at Garongkong station in Barru Regency, South Sulawesi. Using the Kotlin programming language application, Visual Studio Code tools, and MySQL Database. The results of making multimedia applications can display information on train departure schedules, ticket purchases, and automatic time notifications that have been scheduled by the regulator.